Some Common Fixed Point Theorems in Generalized Vector Metric Spaces - Rajesh Shrivastava; Rajendra Kumar Dubey; Pankaj Tiwari (International Journal of Analysis and Applications, 2013)
In this paper we give some theorems on point of coincidence and common fixed point for two self mappings satisfying some general contractive conditions in generalized vector spaces. Our results generalize some well-known recent results in this direction.